Seasonal and Spatial Variation in Growth and Abundance of Zebra Mussel (Dreissena polymorpha) in a Recently Invaded Artificial Lake: Implications for Management - Rolla, Matteo; Consuegra, Sofia; Hall, David J.; Garcia de Leaniz, Carlos (Frontiers in Ecology and Evolution, 2020)
The control of the highly invasive zebra mussel (Dreissena polymorpha) has been flagged as a priority but success has been variable. A better understanding of the growth and drivers of settlement of zebra mussel is necessary for a more efficient management of this invasive species, but seasonal data are still relatively scant. We monitored the seasonal changes in settlement rates, density, and growth of zebra mussel in artificial substrates over one year in Cardiff Bay (UK), an artificial amenity lake invaded by zebra mussels in 2003 and where the species is rapidly expanding. Mean settling rates varied from 4,200 to 6,200 mussel m-2 over June to September mirroring changes in water temperature, and peaked at 17,960 mussels m-2, the highest density reported in Britain. Density was highest at the deepest panels (3 m). Growth varied significantly among sampling stations, with growth taking place during the summer and ceasing during winter and spring. Mixture analysis reveals the existence of multiple cohorts displaying different growth and settling rates and that follow different density dependent mechanisms, being positive density-dependent at low densities, and negative density-dependent at high densities. We suggest this creates the conditions necessary for source and sink metapopulations to develop which may need to be taken into account in management. Targeting mussels for removal in deep waters during the summer and early autumn might prove beneficial, but the existence of contrasting density-dependent mechanisms suggests that removal may be beneficial or counterproductive depending on local conditions.